Causal relationships between immune-related adverse events, immune cell characteristics, and plasma metabolites: insights from Mendelian randomization study - Zhiyuan Shi; Zhao Sun; Dingding Zhang; Lin Zhao (Discover Oncology)
Abstract Background The severe adverse events of immunotherapy have limited its clinical application. Immune cell characteristics and plasma metabolites are probably associated with immune-related adverse events, but current studies have not combined the three dynamically. This study is designed to analyze causality between immune cell characteristics and immune-related adverse events, and the degree to which plasma metabolites mediate it. Methods Data were obtained from genome-wide association studies. Initially, we conducted a two-sample bidirectional Mendelian randomization analysis to assess causal links between immune cell characteristics and immune-related adverse events. Following that, a two-step Mendelian randomization approach was utilized to measure the proportion of total effects mediated by 1400 plasma metabolites. Additionally, sensitivity analyses were conducted at each step to reduce horizontal pleiotropy and heterogeneity. Results We identified 12 immune cell characteristics, and 31 plasma metabolites causally associated with immune-related adverse events. Through mediation effect analysis, 6 immune cell characteristics (CD4 on monocyte,CM CD4 + AC, EM CD4 + %T cell, CD39 + CD4 + AC, HLA DR on CD14 + CD16 + monocyte, CD45RA on TD CD8br) were identified as being correlated with the presence of immune-related adverse events, which were partially mediated by 5 metabolic characteristics (Ornithine to phosphate ratio, 1-palmitoyl-GPE (16:0) levels, 5-hydroxyhexanoate levels, (2,4 or 2,5)-dimethylphenol sulfate levels, 2-palmitoleoyl-GPC (16:1) levels). Among them, 2-palmitoleoyl-GPC (16:1) levels demonstrated the most significant mediating effect, mediating 10.8% (p = 0.0155) of the effect of CD45RA on TD CD8br on immune-related adverse events. The mediating effect is derived through a two-step MR analysis. Conclusions We identified genetic causality among the characteristics of immune cells, plasma metabolites, and immune-related adverse events. By regulating immune cells and plasma metabolites through various methods, it may be possible to alleviate immune-related adverse events. This discovery serves as a valuable reference for the judicious application of immunotherapy in future endeavors.